Framework for Identification of Curriculum Gaps: A Systematic Approach - P., Vinish; Pinto, Prakash; D’Souza, Rio (Journal of Engineering Education Transformations, 2022)
With the rapidly evolving technology, academics and curriculum developers experience criticism for the curriculum being outdated or unable to meet industry requirements. Additionally, the stakeholders involved in curriculum development have divergent views. Therefore, the challenges lie with academicians imparting the necessary skills and preparing the students to be industry-ready. This study takes a closer investigation of the predecessors of the curriculum gap and classifies it into preceding gaps, viz. information gap, benchmarking gap, perception gap, and learning gap. Prior research has focused on overcoming the curriculum gap, while the current study attempts to propose a framework for methodically identifying the curriculum gap. The paper follows online desk research. The framework is developed based on the multidisciplinary literature and thus provide a comprehensive view of the curriculum gap. Hence the study relies heavily on secondary sources of data. The framework transpired from the literature survey of engineering, management, accounting, nursing, and medical sciences disciplines. It, therefore, lacked affiliation to a specific field of study. Also, the stakeholder’s role in the framework may not be appropriate in all contexts as their functions vary within a subject domain and may not exist in some cases. A systematic investigation of the curriculum gap will emphasise the shortcomings in the curriculum, which will assist the faculty in moulding their subject to meet the expectations of stakeholders. The proposed framework aims to expedite the collaboration between the stakeholders and develop a shared vision among all affected. Furthermore, the framework presented benefits academics and curriculum developers by bettering the courses offered and bridging the academia-industry skills gap.